Associations between APOE‐TOMM40 ‘523 haplotypes and limbic system white matter microstructure - Katelyn E. Mooney; Derek B. Archer; Aditi Sathe; Timothy J. Hohman; Ose Kadiri; Melissa Lamar; Konstantinos Arfanakis; Lei Yu; Lisa L. Barnes; Kacie D. Deters (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2025)
Abstract INTRODUCTION We assessed associations between apolipoprotein E Translocase of Outer Mitochondrial Membrane 40 (APOE‐TOMM40)‐‘523 haplotypes and white matter microstructure (WMM) across limbic tracts important for memory and cognition in non‐Hispanic Black and White individuals. METHODS Linear regression models, stratified by APOE and racialized groups, assessed associations between TOMM40‐‘523‐S and limbic tract WMM free‐water (FW) and free‐water‐corrected fractional anisotropy (FAFWcorr). RESULTS Black‐ε4+‐one‐'523‐S carriers had lower FW in the cingulum and inferior longitudinal fasciculus compared to Black‐ε4+‐no‐'523‐S carriers. Additionally, Black‐ε4+‐one‐'523‐S carriers had lower FW in the cingulum, uncinate, and fornix, and higher FAFWcorr in the uncinate compared to Black‐ε4+‐'523‐S/S carriers. White‐ε3/ε3‐‘523‐S/S carriers had lower FAFWcorr in the cingulum and inferior temporal gyrus compared to White‐ε3/ε3‐no‐'523‐S carriers, and lower FAFWcorr in the cingulum compared to White‐ε3/ε3‐one‐‘523‐S carriers. DISCUSSION This supports prior work that ‘523‐S is associated with abnormal aging in White‐ε3/ε3 carriers, but is potentially risk‐mitigating in Black‐ε4+ carriers, while suggesting a differential effect by racialized background of APOE on WMM. Highlights White matter microstructure (WMM) across limbic tracts important for cognition was measured by diffusion MRI. Black apolipoprotein E (APOE) ε4+ carriers with one copy of TOMM40‐‘523‐S had normal aging WMM metrics across several tracts, including the cingulum bundle, uncinate fasciculus, fornix, and inferior longitudinal fasciculus. White APOE ε3/ε3 carriers with two copies of TOMM40‐‘523‐S had abnormal aging WMM metrics in the cingulum bundle and inferior temporal gyrus. APOE associations with aging may differ in racialized groups due to TOMM40‐‘523‐S copy number.